Phytotoxicity and cytotoxicity of Lepidaploa rufogrisea (Asteraceae) extracts in the plant model Lactuca sativa (Asteraceae) - Barroso Aragão, Francielen; Tebaldi Queiroz, Vagner; Ferreira, Adésio; Vidal Costa, Adilson; Fontes Pinheiro, Patricia; Tavares Carrijo, Tatiana; Fonseca Andrade-Vieira, Larissa (Revista de Biología Tropical, 2017)
Lepidaploa rufogrisea is a promising candidate in the search of natural herbicides, with compounds (sesquiterpene lactones-glaucolide B) which have been reported to present with phytotoxic potential against weeds. Thus, this work aimed to accomplish the phytochemical investigation of L. rufogrisea as well as the evaluation of its biological effects on the plant model Lactuca sativa. To this end, different extracts (aqueous, hydroalcoholic and hexane) of L. rufogrisea at different concentrations [0.25, 0.5, 1.0, 2.0 and 4.0 % (m/v)] were evaluated from macroscopic (percentage of germinated seeds, germination speed index and root length) and microscopic analysis (mitotic index and cell cycle alterations) in plantlets (150 per treatment) and meristematic cells (10 000 per treatment) of L. sativa var. Cristina. The extracts decreased the germination speed index and also the root growth of L. sativa plantlets. Cell proliferation was not significantly affected by the extracts. However, some chromosome and nuclear alterations in the mitotic spindle were observed, due to the interference of allelochemicals present in L. rufogrisea. Moreover, the plant model L. sativa demonstrated to be efficient for this kind of studies.